A Fluorescent Probe Containing Triphenylamine‐Benzofuranone Moiety for Detecting Cysteine and Imaging in Living Pulmonary Cells Under Hypercapnia - Wu, Xiao‐Ping; Yang, Na; Liu, Qing‐Qing; Zhu, Zhong‐Quan (Luminescence (Chichester, England), 2024)
ABSTRACT In this work, a fluorescent probe TPB‐Cys derived from triphenylamine‐benzofuranone was developed for monitoring the cysteine (Cys) level and imaging in living pulmonary cells under hypercapnia condition. A systematic hypoxia module was tried to cover both the in‐solution test and pulmonary cellular imaging. The hypoxia condition did not obviously affect the fluorescence response signal during the in‐solution test. The fluorescence signal at 540 enhanced in a dose‐dependent enhancement along with the increase of the Cys concentration. The probe showed the advantages including relatively long linear range, high sensitivity, high stability, and high selectivity. With low cyto‐toxicity, TPB‐Cys achieved the monitoring of the endogenous Cys level in living pulmonary cells. Furthermore, it also realized the visualization of the affection of the hypoxia and hypoxia recovered conditions. This work was informative for both the accurate diagnosis and potential medical techniques. A fluorescent probe TPB‐Cys derived from triphenylamine‐benzofuranone was developed for monitoring the cysteine level and imaging in living pulmonary cells under hypercapnia condition. TPB‐Cys achieved the monitoring of the endogenous Cys level in living pulmonary cells, while it also realized the visualization of the affection of the hypoxia and hypoxia recovered conditions.